IT GOVERNANCE CAPABILITY LEVEL IDENTIFICATION OF COBIT 2019 AT THE RSUP PROF. DR. R.D. KANDOU, MANADO, NORTH SULAWESI - Mambu, Joe Yuan; Lontaan, Rolly Junius; Lompoliu, Erienika; Salindeho, Jannice; Sambul, Jenifer (Informatics Engineering Department of Halu Oleo University, 2022)
In terms of technology, governance can be implemented effectively and efficiently if it can provide functionality or value that applies to businesses of all sizes and types. IT governance design can help you explore design factors that influence governance and includes a workflow for planning a governance system for your enterprise. Control Objectives for Information and Related Technologies (COBIT) is a framework created by ISACA that contains guidance or guidance documents that may be useful to auditors, users, and management. COBIT is an internationally recognized and applied best practice for information, information technology, and organizational risk which can be used to define information technology to maximize IT control. As it is required to improve IT service, the design of IT governance was conducted at the Central Unit Hospital (RSUP) Prof. Kandou, Manado, North Sulawesi, using the latest version of COBIT, COBIT 2019. The following is an explanation of the priorities of Malayang Hospital. Governance below 25 points is proficiency level 1. The results shows that there are five objectives that becomes main priority (reaching level 4): EDM03, APO12, BAI02, BAI03 and BAI05. These objectives are the ones recommended to be audited. The second tier that may also suggested to be audited are objectives with capability level 3: APO07, APO08, BAI01, BAI07, DSS01, DSS02 and MEA01.Keywords; COBIT 2019, IT Governance, RSUP Prof. Kandou Malalayang